Imaging the intratumoral-peritumoral extracellular pH gradient of gliomas - Coman, Daniel; Huang, Yuegao; Rao, Jyotsna U.; De Feyter, Henk M.; Rothman, Douglas L.; Juchem, Christoph; Hyder, Fahmeed (NMR in biomedicine, 2016)
Solid tumors have an acidic extracellular pH (pHe) but near neutral intracellular pH (pHi). Because acidic pHe milieu is conducive to tumor growth and builds resistance to therapy, simultaneous mapping of pHe inside and outside the tumor (i.e., intratumoral‐peritumoral pHe gradient) fulfills an important need in cancer imaging. We used Biosensor Imaging of Redundant Deviation in Shifts (BIRDS), which utilizes shifts of non‐exchangeable protons from macrocyclic chelates (e.g., 1,4,7,10‐tetraazacyclododecane‐1,4,7,10‐tetrakis(methylene phosphonate) or DOTP8−) complexed with paramagnetic thulium (Tm3+) ion, to generate in vivo pHe maps in rat brains bearing 9L and RG2 tumors. Upon TmDOTP5− infusion, MRI identified the tumor boundary by enhanced water transverse relaxation and BIRDS allowed imaging of intratumoral‐peritumoral pHe gradients. The pHe measured by BIRDS was compared with pHi measured with 31P‐MRS. In normal tissue, pHe was similar to pHi, but inside the tumor pHe was lower than pHi. While the intratumoral pHe was acidic for both tumor types, peritumoral pHe varied with tumor type. The intratumoral–peritumoral pHe gradient was much larger for 9L than RG2 tumors because in RG2 tumors acidic pHe was found in distal peritumoral regions. The increased presence of Ki‐67 positive cells beyond the RG2 tumor border suggested that RG2 was more invasive than the 9L tumor. These results indicate that extensive acidic pHe beyond the tumor boundary correlates with tumor cell invasion. In summary, BIRDS has sensitivity to map the in vivo intratumoral–peritumoral pHe gradient, thereby creating preclinical applications in monitoring cancer therapeutic responses (e.g., with pHe‐altering drugs). Copyright © 2016 John Wiley & Sons, Ltd. Simultaneous mapping of pHe inside and outside the tumor fulfills an important need in cancer imaging. We used Biosensor Imaging of Redundant Deviation in Shifts (BIRDS) to generate in vivo pHe maps in rat brain bearing 9L and RG2 tumors. Upon TmDOTP5‐ infusion, MRI identified the tumor boundary by enhanced water transverse relaxation and BIRDS allowed imaging of intratumoral‐peritumoral pHe gradients, which were larger for 9L than RG2 tumors. Extensive acidic pHe beyond tumor boundary correlates with tumor cell invasion.